2022
DOI: 10.1371/journal.pone.0274102
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of substance use and associated factors among secondary school adolescents in Kilimanjaro region, northern Tanzania

Abstract: Background Substance use among school-going adolescents increases the risk of developing mental disorders, addiction, and substance use disorders. These may lead to poor academic performance and reduced productivity, which affects adolescent lives. The study aimed to determine the prevalence of substance use and associated factors among secondary school adolescents in the Kilimanjaro region, northern Tanzania. Methodology The study used secondary data from a cross-sectional survey of adolescents aged 10–19 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The European Monitoring Centre for Drugs and Drug Addiction (2023) reported that in 2022, cannabis use among the EU population aged 15 to 34 was 15.1% (15.3 million), with males being twice as likely as females to report use [19]. Mavura et al discovered a 12.8% prevalence of substance use among Tanzanian adolescents, with reported use of cocaine, heroin, and marijuana [20]. Haddad et al [21] found Jordanian students to be knowledgeable about substance abuse's harmful effects on the body and society, though lacking in-depth knowledge [21].…”
Section: Discussionmentioning
confidence: 99%
“…The European Monitoring Centre for Drugs and Drug Addiction (2023) reported that in 2022, cannabis use among the EU population aged 15 to 34 was 15.1% (15.3 million), with males being twice as likely as females to report use [19]. Mavura et al discovered a 12.8% prevalence of substance use among Tanzanian adolescents, with reported use of cocaine, heroin, and marijuana [20]. Haddad et al [21] found Jordanian students to be knowledgeable about substance abuse's harmful effects on the body and society, though lacking in-depth knowledge [21].…”
Section: Discussionmentioning
confidence: 99%
“…Despite measures to control substance abuse being put in place, these vices remain highly prevalent, especially among adolescents and youths [49,74,[76][77][78][79]. These substances have been reported to cause mental health problems to abusers in previous studies [21,33,80,81].…”
Section: Discussionmentioning
confidence: 99%
“…A study in Nepal reported increased abuse of alcohol, cigarettes, and illegal drugs among medical students [72]. Similarly, a Tanzanian study also reported high abuse of alcohol and cigarettes among secondary school adolescents [74]. In Nigeria, a study found that codeine-containing products, tramadol, alcohol, and cannabis were highly abused by adolescents and youths due to emotional, economic, and societal problems [75].…”
Section: Discussionmentioning
confidence: 99%